2022
DOI: 10.3389/fonc.2022.857062
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complications on Oncological Outcomes of Colorectal Cancer Patients After Primary Surgery: A Propensity Score Matching Analysis

Abstract: PurposeThe purpose of this study is to explore the oncologic outcomes of complications on colorectal cancer (CRC) patients who underwent primary surgery using a propensity score matching (PSM) analysis.MethodsA retrospective study was conducted from Jan 2011 to Jan 2020 in a clinical center. The overall survival (OS) and disease-free survival (DFS) were compared among the no complications group, the major complications group and the minor complications group.ResultsA total of 4250 CRC patients who underwent ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In recent years, anastomosis and surgical techniques have developed considerably, but the incidence of post-operative complications in RC has not been significantly reduced ( 9 12 ). Several previous studies have shown that post-operative complications affected the prognosis of RC ( 28 30 ). Therefore, it was necessary to develop a predictive nomogram for major post-operative complications in RC.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, anastomosis and surgical techniques have developed considerably, but the incidence of post-operative complications in RC has not been significantly reduced ( 9 12 ). Several previous studies have shown that post-operative complications affected the prognosis of RC ( 28 30 ). Therefore, it was necessary to develop a predictive nomogram for major post-operative complications in RC.…”
Section: Discussionmentioning
confidence: 99%
“…The serum albumin, as an indicator of the nutritional status of the body, was associated with system inflammation [ 32 , 33 ]. The decreased albumin had huge influence on recovery after surgery [ 34 , 35 ], which might lead to severe postoperative complication [ 4 , 36 , 37 ]. LDH was involved in tumor metabolism [ 38 , 39 ], and elevated LDH was associated with immune suppression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 – 3 ]. Although the surgical procedures and neoadjuvant chemoradiotherapies had become more and more mature, the prognosis of CRC was still not optimistic [ 4 , 5 ]. It was reported that there were many biomarkers affecting prognosis in CRC patients, including lactate dehydrogenase (LDH), albumin [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Okamura et al ( 20 ) reported that elderly patients with CRC were more suitable for laparoscopic surgery. Compared with traditional open surgery, laparoscopic surgery had a smaller incision, less IBL, a shorter postoperative hospital stay and lower postoperative complications and postoperative mortality ( 29 , 30 ). However, in the present study, no significant difference in surgical approach was found between the larger and the smaller IBL groups.…”
Section: Discussionmentioning
confidence: 99%